Experimental verification of null steering by element positionperturbations - Dawoud, M.M. (1992)
Null steering in an adaptive array is realized by element position perturbations. Small position perturbations are assumed, which is valid when the number of imposed nulls is small compared to the number of array elements. The null steering has been achieved for an eight-element monopole array over a ground plane. The array illumination function is used solely for pattern formation and can also be used for main beam steering. Single and double nulls are realized in the sidelobe region. The experimental results prove the validity of null steering by controlling the element positions